PENGEMBANGAN MEDIA PEMBELAJARAN POUBASA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS II SD N SURYODININGRATAN 2 - Ilham Nugroho; Bahtiyar Heru Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This investigation was implemented with the goal of exploring: (1) the process of developing the POUBASA learning platform to develop students' early literacy skills, (2) the attainability of POUBASA learning tool, and (3) the efficacy of POUBASA media to advance basic reading skills of level II students of SD Negeri Suryodiningratan 2. This research uses a study and creation method (Research and Development) by a 4-D pattern (Establish, Plan, Build, and Spread). The investigation was undertaken at SD Negeri Suryodiningratan 2, Mantrijeron District, Yogyakarta City in the 2024/2025 academic year. The research findings indicate that: (1) the POUBASA platform was developed for Indonesian language lessons with a focus on early reading, using attractive visual displays and pop-up elements, (2) the media was declared feasible with the results of the media validator validation showing 80% (good category) and the substance validator showing 100% (very good category); the reaction of the teaching staff was 100% and the students were 92.12% (very feasible category), (3) the POUBASA media was proven to be effective based on the paired sample t-test which demonstrated a significance score (Sig. 2-tailed) of 0.000 < 0.05, indicating that this signifies one existed in existence significant increase inside this initial reading achievement of students after using the media. Thus, POUBASA is declared valid, feasible, and effective as an educational tool.